Maternal serum progesterone level in preeclampsia - Chowdhury, Shiuly; Ferdous, Jannatul; Nahar, Khadiza Nurun; Mahmood, Sharmeen (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This study was performed to find out a relationship between the levels of progesterone with (n=30) and without (n=48) preeclampsia. The age and body mass index of the participants along with their gestational age, gravidity and parity were harmonized. The serum progesterone and serum androgens such as total testosterone, free testosterone, and dehydroepiandrosterone sulfate levels were investigated. The results revealed that although the serum progesterone level was significantly low among the participants with preeclampsia (182.7 ± 29.4 vs 281.7 ±16.2 ng/mL; p<0.001) but the total and free testosterone levels were found to be significantly higher than the healthy normotensive participants (2.5 ± 0.6 vs. 1.9 ± 0.1 nmol/dL; p= 0.041 and 2.2 ± 0.3 vs. 1.4 ± 0.2 pg/mL, respectively, p=0.035). In conclusion, the serum progesterone level was low in pregnant women having preeclampsia.